A vaccine targeting basic fibroblast growth factor elicits a protective immune response against murine melanoma. Issue 6 (3rd June 2018) - Zhang, Xiaoping; Li, Neng-Lian; Guo, Chao; Li, Ying-Dong; Luo, Lu-Lu; Liu, Yong-Qi; Duan, Yun-Yan; Li, Zhen-Dong; Xie, Xiao-Rong; Song, Hai-Xia; Yang, Li-Ping; An, Fang-Yu
ABSTRACT: Tumor growth and metastasis are closely related to angiogenesis. Basic fibroblast growth factor(bFGF) is an angiogenic factor, and up-regulated expression of bFGF plays a crucial role in the development and metastasis of melanoma. Therefore, in this study, we sought to achieve antitumor activity by immunity targeting bFGF which would inhibit tumor angiogenesis and simultaneously induce bFGF specific cytotoxic T lymphocytes to kill melanoma cells. A human bFGF protein was used as exogenous antigen, coupled with a saponin-liposome adjuvant formulation to enhance CTL response. The results showed that the immunity induced strong immune response and produced prominent anti-cancer activities. CD31 immunohistochemistry and alginate-encapsulated tumor cell assay displayed that tumor angiogenesis was effectively inhibited. Further, the higher production of IFN-γ and cytotoxic T lymphocyte killing assay suggested that the anti-cancer activities may mainly depend on cellular immune response, which could cause the inhibition of tumor angiogenesis and specific killing of tumor cells by bFGF-specific cytotoxic T lymphocytes. We concluded that immunotherapy targeting bFGF may be a prominent strategy for melanoma, and that the adjuvant formulation of saponin-liposome is very desirable in enhancing cytotoxic T lymphocytes response.